Glacial activity and paleoclimatic evolution records in the Cosmonaut Sea since the last glacial maximum - Chen, Dong; Ge, Qian; Lei, Ziyan; Zhou, Bingfu; Han, Xibin (Frontiers in Marine Science, 2024)
This research explored the origin and paleoenvironmental significance of sediments from the Cosmonaut Sea, Antarctica, focusing on the period since the Last Glacial Maximum (LGM, 26,000 cal a BP). Sediment samples from core ANT37-C5/6-07 were subjected to AMS14C dating, clay-mineral assemblage analysis, grain size evaluation, and geochemical testing. Results indicated illite as the dominant clay mineral (average 46%), followed by kaolinite (22%) and smectite (21%), with chlorite (11%) being the least abundant. Comparison with previous studies suggested that these sediments are largely derived from weathered material from Prydz Bay and Enderby Land coastal regions. The study of mineral ratios, geochemical elements, and sediment grain size, alongside δ18O values from the East Antarctica EDML ice core, revealed that the ice sheet in the study area retreated around 18600 cal a BP, melted more markedly during 16800-15000 cal a BP, tended to expand during 14800-13500 cal a BP, and then the ice sheet remained in a state of retreat until it expanded again around 5000 cal a BP. It is largely synchronous with the phased changes in the Antarctic climate since the LGM (26ka) of the Cosmonaut Sea. Notably, the sediment record aligns with major paleoclimatic events, including Heinrich Stadial 1 and the Younger Dryas in the northern hemisphere and the Antarctic cold reversal, reflecting a climatic ‘seesaw’ effect. These findings suggest that the sedimentary record in the Cosmonaut Sea is a sensitive indicator of climatic conditions, highlighting a history of glacial movements and revealing East Antarctica’s climatic fluctuations. Additionally, the research indicates that the regional ice sheet is more sensitive to climatic changes than previously believed, underscoring its instability.